Analysis on hybrid nanofluid over a shrinking sheet with transpiration and uniform shear flow - Azmi, Muhammad Aqil; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2022)
This study is conducted to analyse the effect of the uniform shear flow and transpiration over the shrinking sheet on hybrid nanofluid. A similarity transformation is used to convert the governing equation from partial differential equations to ordinary differential equations using a set of similarity variables, and then the solutions are obtained using the shooting technique with RKF45 method in Maple software. The effects of several governing parameters such as transpiration parameter, shrinking parameter and nanoparticles volume fraction for alumina oxide and copper on the flow and heat transfer characteristics are presented in tables and graphs. Results elucidate that the skin friction coefficient decreases while the local Nusselt number increases as the shrinking parameter increased in regular fluid in the absence of transpiration. It is also found that in the presence of transpiration, alumina nanoparticle volume fraction decreases the heat transfer rate at the surface while it increases the skin friction coefficient. However, for copper nanoparticle volume fractions, the opposite results are obtained.